EVALUASI PEKERJAAN ULANG (REWORK) PADA PROYEK KONSTRUKSI JALAN DI KOTA BANDA ACEH - Muhammad Rizal; Mochammad Isya; Sofyan M. Saleh (Prodi Magister Teknik Sipil Unsyiah, 2018)
The construction project has a target of either completion time or cost, as well as road construction projects. Projects that are delayed due to rework are at risk both to the owner and beneficiary if the project is a means and infrastructure used by the community. Rework greatly affects the performance and productivity of workers in the field. Therefore, the purpose of this study is to determine what dominant factors that cause the occurrence of rework and know the work that often the occurrence of rework. The research method is descriptive with quantitative technique. Samples were taken from the population and determined by using Slovin formula, and it obtained as many as 51 companies. Random sampling is adapted to select respondent that representing the target companies. The result of analysis shows that the dominant factor caused the occurrence of rework namely lack of control with the value of frequency index (FI) 0.80; weather (FI value 0.79); an overcrowded schedule (FI value 0.78); wrong decision (FI value 0,78); lack of field information (FI value 0.78); lack of knowledge of specification (FI value of 0.73); and less experienced workers (FI value of 0.68). Interpretation of scores sometimes got 6 factors of rework, for example, less equipment with a value of FI 0.49; design changes with FI value of 0.49; local conditions (project disruption) with an FI value of 0.49; number of overtime work with value of FI 0,47; detail is not clear with value of FI 0,45; and lack of constructability with FI value of 0.45. While the frequent activities of rework are the widening of pavement and road shoulders, granular pavement and concrete pavement cement, asphalt pavement, and a returning of minor conditions and work.